Kontribusi Teori Belajar Kognitivisme David P. Ausubel dan Robert M. Gagne dalam Proses Pembelajaran - Muhammad Syaikhul Basyir; Aqimi Dinana; Aulia Diana Devi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to describe the theory of learning cognitivism in learning according to the views of David P. Ausebel and Robert M. Gagne. This research uses a qualitative approach to content analysis and descriptive research design. The results of this study show that cognitive learning theory is more concerned with the learning process than the learning outcomes themselves. Ausubel's theory of meaningful learning occurs when a person learns by associating new phenomena into the structure of their knowledge. In the process of learning a person constructs what he has learned and associates new experiences, phenomena and facts into the structure of their knowledge. According to Rober M. Gagne, learning is a set of processes that are internal to each individual as a result of the transformation of stimuli derived from external events in the environment of the individual concerned (conditions). According to Robert Gagne, learning should be able to give rise to learning events and cognitive processes.